2011
DOI: 10.1111/j.1365-2966.2011.18613.x
|View full text |Cite|
|
Sign up to set email alerts
|

Placing limits on the stochastic gravitational-wave background using European Pulsar Timing Array data

Abstract: Direct detection of low-frequency gravitational waves (GWs, 10(-9) to 10(-8) Hz) is the main goal of pulsar timing array (PTA) projects. One of the main targets for the PTAs is to measure the stochastic background of gravitational waves (GWB) whose characteristic strain is expected to approximately follow a power-law of the form h(c)(f) = A(f /yr(-1))(alpha), where f is the GW frequency. In this paper we use the current data from the European PTA to determine an upper limit on the GWB amplitude A as a function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
246
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(249 citation statements)
references
References 27 publications
3
246
0
Order By: Relevance
“…It is widely considered that a stochastic GW background due to the combined emission from a large number of individual SMBBHs over cosmological volume (e.g., Sesana 2013b; Ravi et al 2014, for recent work) provides the most promising target; indeed, some studies suggested that a detection of this type could occur as early as 2016 (Siemens et al 2013). Analyses of actual PTA data have previously focused on a search for such a GW background, leading to more and more stringent constraints on the fractional energy density of the background (Jenet et al 2006;Yardley et al 2011;van Haasteren et al 2011;Demorest et al 2013;Shannon et al 2013). Over the past few years interest has grown substantially regarding the prospects of detecting single-source GWs using PTAs, for example, for individual SMBBHs (Sesana et al 2009;Lee et al 2011;Mingarelli et al 2012;Ravi et al 2015), for GW memory effects associated with SMBBH mergers (Seto 2009;Cordes & Jenet 2012;Madison et al 2014), for GW bursts (Pitkin 2012) and for unanticipated sources (Cutler et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely considered that a stochastic GW background due to the combined emission from a large number of individual SMBBHs over cosmological volume (e.g., Sesana 2013b; Ravi et al 2014, for recent work) provides the most promising target; indeed, some studies suggested that a detection of this type could occur as early as 2016 (Siemens et al 2013). Analyses of actual PTA data have previously focused on a search for such a GW background, leading to more and more stringent constraints on the fractional energy density of the background (Jenet et al 2006;Yardley et al 2011;van Haasteren et al 2011;Demorest et al 2013;Shannon et al 2013). Over the past few years interest has grown substantially regarding the prospects of detecting single-source GWs using PTAs, for example, for individual SMBBHs (Sesana et al 2009;Lee et al 2011;Mingarelli et al 2012;Ravi et al 2015), for GW memory effects associated with SMBBH mergers (Seto 2009;Cordes & Jenet 2012;Madison et al 2014), for GW bursts (Pitkin 2012) and for unanticipated sources (Cutler et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, these constraints are strongly dependent on uncertain string physics, most notably the network loop production scale and the nature of string radiation from cusps, i.e., points on the strings approaching the speed of light c. The most optimistic constraint based on the European Pulsar Timing Array is Gµ/c 2 < 4.0 × 10 −9 (van Haasteren et al 2011), but a much more conservative estimate of Gµ/c 2 < 5.3 × 10 −7 can be found in Sanidas et al (2012), together with a string parameter constraint survey and an extensive discussion of these uncertainties. Such gravitational wave limits do not apply to global strings or to strings for which other radiative channels are available.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some of the binaries may be sufficiently luminous to stand out above the diffuse background level and could be individually observed [24,30]. The search for GWs from a SMBHB background [25][26][27][28] and from individual resolvable sources [29][30][31][32][33][34] has recently catalysed the PTA GW search effort, and it is plausible that in the next 5 to 10 years GWs could indeed be detected. If not, stringent constraints can be placed on aspects of the assembly history of SMBHBs [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%